0258 Positive and Negative Emotions are Differentially Associated with Sleep Duration and Quality in Adolescents. (27th April 2018) - Shen, L; Schie, Jv; Ditchburn, G; Brook, L; Bei, B
Abstract: Introduction: Insufficient and poor-quality sleep is common in adolescents, and are associated with affective disturbances. Most past studies focused on examining the associations between sleep and negative emotions, neglecting positive affect and emotional experiences. The current study addresses this gap by simultaneously examining associations between self-reported sleep duration and quality, with positive affect, negative affect, and happiness in adolescents. Methods: A large community sample of 4, 582 adolescents (69.4% females, M±SD age: 14.55 ± 1.74 years) completed the following measures: typical sleep duration and quality, Positive and Negative Affect Schedule, and Subjective Happiness Scale. Structural equation modelling was used to examine associations between sleep duration and quality on positive affect, negative affect, and happiness. Age and sex were controlled for. Results: Both shorter and poorer sleep were significantly associated with lower positive affect, higher negative affect, and lower happiness. Overall, compared to sleep duration, sleep quality demonstrated stronger associations with all three measures of emotions. Sleep duration and quality exhibited differential associations with positive and negative emotions. Shorter sleep duration had a greater impact on dampening positive emotions (happiness, followed by positive affect), while poor sleep quality demonstrated stronger associations with elevating negative affect. Conclusion: This is the first study to simultaneously examine sleep duration and quality with positive and negative emotions in adolescents. Compared to sleep duration, adolescents' perceived sleep quality had a stronger impact on their emotions. Positive and negative emotions are also differentially associated with sleep duration and quality. Poorer sleep quality may be a risk factor for affective disturbances, while longer sleep duration may promote longer-term positive emotions (happiness). Given that adolescence marks increased vulnerabilities to affective disturbances, these findings have practical implications for adolescents' psychological wellbeing. Support (If Any): Monash Graduate Scholarship, Monash International Postgraduate Research Scholarship, In-kind contributions from People Diagnostix.